Responsibility Of Perpetrators Of The Criminal Act Of Using Fake Diplomas In The Nomination Of Legislative Members (Study Of Decision No. 105/PID/2021/PT.TJK JO. Decision No. 43/PID/2021/PN LIW) - Safitri, Wulandini Fayza; Firganefi, Firganefi; Tamza, Fristia Berdian (Multidisciplinary Journals, 2024)
A fake diploma or Aspal diploma (original but fake) is a criminal act that meets the formulation of the provisions of Article 263 of the Criminal Code and Article 264 of the Criminal Code, because it can give rise to a right. The diploma forgery was carried out by the defendant Sj bin BL (deceased) The approach to the problem in this research used a normative juridical and empirical juridical approach. Processing of the data obtained is carried out by means of data selection, data classification, and data preparation. Data analysis uses a qualitative approach.